2017
DOI: 10.1016/j.bioactmat.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release and biocompatibility of polymer/titania nanotube array system on titanium implants

Abstract: Bacterial infection and tissue inflammation are the major causes of early failure of titanium-based orthopedic implants; thus, surgical implants with tunable drug releasing properties represent an appealing way to address some of these problems of bacterial infection and tissue inflammation in early age of orthopedic implants. In this work, a hybrid surface system composed of biodegradable poly(lactic-co-glycolic acid) (PLGA) and titania nanotubes (TNTs) has been successfully constructed on Ti implants with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 38 publications
(36 reference statements)
1
37
0
Order By: Relevance
“…In the second study, TNTs implants were coated with basic fibroblast growth factor (bFGF) in combination with a biodegradable polymer (PLGA) and analyzed by histomorphometry also after 12 weeks . The results of both studies showed a significant increase in bone cell adhesion and proliferation for the groups containing growth factors when compared to the anodized‐only control groups, suggesting a positive influence of the incorporation of growth factors to the TNTs surfaces in terms of the quality and quantity of the observed bone formation …”
Section: Drug Delivery Systemmentioning
confidence: 93%
See 1 more Smart Citation
“…In the second study, TNTs implants were coated with basic fibroblast growth factor (bFGF) in combination with a biodegradable polymer (PLGA) and analyzed by histomorphometry also after 12 weeks . The results of both studies showed a significant increase in bone cell adhesion and proliferation for the groups containing growth factors when compared to the anodized‐only control groups, suggesting a positive influence of the incorporation of growth factors to the TNTs surfaces in terms of the quality and quantity of the observed bone formation …”
Section: Drug Delivery Systemmentioning
confidence: 93%
“…However, the possibility of including an antibiotic agent directly at the implantation site makes this alternative significantly attractive, with possible greater therapeutic effectiveness involved with a significantly lower drug dosage . Vancomycin, penicillin, antimicrobial peptides and gentamicin are examples of possible antibiotic agents mentioned in the literature as potentially incorporable to TNTs, as they are known inhibitors of bacterial growth responsible for diseases in surrounding tissues, and also possibly able to minimize the local tissue inflammatory response …”
Section: Drug Delivery Systemmentioning
confidence: 99%
“…Therefore, a plethora of fabrication techniques have been demonstrated in the literature to synthesize such nanotubes from different materials. Specically, huge interest has been shown in the synthesis of titania nanotubes and their applications due to their biocompatibility, [1][2][3] antimicrobial properties, 4,5 high chemical stability, specic surface area, and catalytic activity. [6][7][8] In addition, the high UV absorption and the possibility to modify the band gap promote titania as a good candidate for photocatalysis, making it useful for producing sunscreen materials 9 and in water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the literature is pervaded with coating methods designed to resolve a combination of the implant failure modes listed above by developing multifunctional implant modification procedures [2,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. While it is known that modifying the topography of the implant surface on the nanoscale has shown to be effective in terms of increasing osteogenic phenomena and lessening rejection [43], these coatings do not effectively prevent bacterial colonization.…”
Section: Introductionmentioning
confidence: 99%